When Girls Give Birth Babies: Case Study of ChildMarriage in Sumenep Madura - Masthuriyah Sa'dan (Jurnal Perempuan, 2016)
The Madurese never refuse a proposal of a man who first comes. Therefore, Madurese girls would marry at a much younger age in their teenage years even before they reach 12 years old. Child marriages leads to the following severe problems: domestic violence, infidelity, divorce, problems of pregnancy and birth. In this context, there is injustice toward girls in the process of marriage and when the marriage happens. Psychologically, the girls are not ready enough to face domestic taks as a wife and mother. Besides that, girls also face a life-threatening situation during pregnancy and childbirth because of the unprepared reproductive organs. Therefore, a judicial review to the Constitutional Court regarding the minimum age of marriage for women from the age of 16 in article 7 of Law No. 1 of 1974 to the age of 18 years is a solution to eliminate the increasing child marriage and reduce the rate of maternal death and child-mortality rate.